Down regulation of GALNT3 contributes to endothelial cell injury via activation of p38 MAPK signaling pathway. (February 2016) - Guo, Liwei; Wang, Laiyuan; Li, Hongfan; Yang, Xueli; Yang, Bin; Li, Mengting; Huang, Jianfeng; Gu, Dongfeng
Abstract: Objective: The GALNT3 gene encodes polypeptide N-acetylgalactosaminyl transferase 3 (GalNAc-T3), a member of the GalNAc-Ts family that transfers the N-acetylgalactosamine to the hydroxyl group of serine and threonine residue in the first step of O-linked oligosaccharide biosynthesis. Emerging evidences have linked GalNAc-Ts family to coronary artery disease (CAD). However the effect of GALNT3 in CAD is unknown. The present study investigated the function and mechanisms of GALNT3 gene in endothelial injury. Methods and results: The GALNT3 mRNA level was decreased by 48.2% in CAD patients (n = 58), compared with that of controls (n = 120). Expression of GALNT3 was also decreased in human umbilical vein endothelial cells (HUVECs) treated with CAD sera and subjected to hypoxia in vitro . Knockdown of GALNT3 promoted apoptosis and up-regulated the expression of matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase-14 (MMP-14). Conversely, overexpression of GALNT3 significantly inhibited HUVECs apoptosis and down-regulated the expression of MMP-2 and MMP-14 genes, in addition, overexpression of GALNT3 attenuated hypoxia-induced apoptosis and expression of MMP-2 and MMP-14. Finally, the ratio of cytosolic p-p38 MAPK/p38 MAPK expression was significantly increased with GALNT3 knockdown and lower with GALNT3 overexpression, while the p38 MAPK inhibitor SB203580 blocked the effects of GALNT3 knockdown. Conclusions: Expression of GALNT3 was reduced in CAD patients, and down regulation of GALNT3 contributed to endothelial injury by promoting apoptosis and up-regulating the expression of MMP-2 and MMP-14 genes via p38 MAPK activation. GALNT3 may be a potential target for future therapeutic intervention for CAD. Highlights: Expression of GALNT3 was reduced in CAD patients and in vitro hypoxic HUVECs. Downregulation of GALNT3 promoted HUVECs apoptosis and MMP-2 and MMP-14 expression. Downregulation of GALNT3 induced endothelial injury via p38/MAPK activation. GALNT3 may be a potential target for future therapeutic intervention for coronary artery disease.